2016
DOI: 10.1177/0961203316652491
|View full text |Cite
|
Sign up to set email alerts
|

Targeted B cell therapies in the treatment of adult and pediatric systemic lupus erythematosus

Abstract: Belimumab (Benlysta) is a fully-humanized monoclonal antibody that inhibits B-lymphocyte stimulator (also known as B cell activating factor) and was approved by the U.S. Federal Drug Administration and European Medicines Evaluation Agency for treatment in adults with autoantibody-positive systemic lupus erythematosus (SLE). Rituximab (Rituxan) is a chimeric anti-CD20 monoclonal antibody targeting B lymphocytes. This review discusses the key findings of the phase III trials in adults with SLE and of real-world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 64 publications
(112 reference statements)
1
8
0
5
Order By: Relevance
“…Of interest, systemic lupus erythematosus (SLE) ranked first. SLE is due to the inability of individual’s immune system to distinguish between self and non-self-antigens, resulting in the production of antibodies against self-antigens and triggering an over-active inflammatory response (Hui-Yuen et al 2016 ). Since impaired B cells are typical characteristics of SLE and B cells are the main cells involved in humoral immunity (Bakshi et al 2018 ), this implies that in ES-LUAD patients, the occurrence of rapid recurrence may be closely related to humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, systemic lupus erythematosus (SLE) ranked first. SLE is due to the inability of individual’s immune system to distinguish between self and non-self-antigens, resulting in the production of antibodies against self-antigens and triggering an over-active inflammatory response (Hui-Yuen et al 2016 ). Since impaired B cells are typical characteristics of SLE and B cells are the main cells involved in humoral immunity (Bakshi et al 2018 ), this implies that in ES-LUAD patients, the occurrence of rapid recurrence may be closely related to humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…45-48 For example, the phase III RCTs BLISS-52 and BLISS-76 found that BMB plus standard of care therapy significantly reduced the rate of disease flares, permitted lower corticosteroid doses and decreased serologic SLE activity when compared to placebo. 4548…”
Section: Discussionmentioning
confidence: 99%
“…44 Although there is scant literature on the use of BMB in JSLE, improved clinical and serological outcomes were observed after BMB therapy, 32 corresponding with earlier adult studies. [45][46][47][48] For example, the phase III RCTs BLISS-52 and BLISS-76 found that BMB plus standard of care therapy significantly reduced the rate of disease flares, permitted lower corticosteroid doses and decreased serologic SLE activity when compared to placebo. [45][46][47][48] The use of BMB for JSLE in only one study 32 suggests that there is much more to be done for JSLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…BLyS may increase the ability of autoreactive B cells to escape regulatory mechanisms and differentiate into autoantibody-secreting plasma cells [34]. Belimumab has been shown to be effective in autoantibody-positive adult SLE patients with moderately active disease whose clinical manifestations are predominantly mucocutaneous and/or musculoskeletal and emerging data confirms that pSLE patients with similar characteristics also respond favorably to belimumab, in particular, suggesting a potential role for belimumab as a steroid-sparing agent [35]. …”
Section: Introductionmentioning
confidence: 99%